Does reduction in mycophenolic acid dose compromise efficacy regardless of tacrolimus exposure level? An analysis of prospective data from the Mycophenolic Renal Transplant (MORE) Registry. (2nd August 2012) - Langone, Anthony; Doria, Cataldo; Greenstein, Stuart; Narayanan, Mohanram; Ueda, Kimi; Sankari, Bashir; Pankewycz, Oleh; Shihab, Fuad; Chan, Laurence
Abstract Prospective data are lacking concerning the effect of reduced mycophenolic acid (MPA) dosing on efficacy and the influence of concomitant tacrolimus exposure. The Mycophenolic Renal Transplant (MORE) Registry is a prospective, observational study of de novo kidney transplant patients receiving MPA therapy under routine management. The effect of MPA dose reduction, interruption, or discontinuation (dose changes) was assessed in 870 tacrolimus‐treated patients: 375 (43.1%) reduced tacrolimus (≤7 ng/mL at baseline) and 495 (56.9%) standard tacrolimus (>7 ng/mL); enteric‐coated mycophenolate sodium 589 (67.7%) and mycophenolate mofetil 281 (32.3%). During baseline to month 1, months 1–3, months 3–6, and months 6–12, 9.3% (78/838), 16.6% (132/794), 20.7% (145/701), and 13.1% (70/535) patients, respectively, required MPA dose changes. These patients experienced an increased risk of biopsy‐proven acute rejection at one yr with tacrolimus exposure either included in the model (hazard ratio [HR] 2.60, 95% CI 1.28–5.29, p = 0.008) or excluded (HR 2.58, 95% CI 1.28–5.23, p = 0.008). MPA dose changes were significantly associated with one yr graft failure when tacrolimus exposure was included (HR 2.23; 95% CI 1.01–4.89, p = 0.047) but not when tacrolimus exposure was excluded (HR 2.16; 95% CI 0.99–4.79; p = 0.054). These results suggest that reducing or discontinuing MPA can adversely affect graft outcomes regardless of tacrolimus trough levels.